Velopharyngeal Muscle Morphology in Children With Unrepaired Submucous Cleft Palate: An Imaging Study. (March 2021) - Schenck, Graham C.; Perry, Jamie L.; O'Gara, Mary M.; Linde, Amy Morgan; Grasseschi, Mitchell F.; Wood, Robert J.; Lacey, Martin S.; Fang, Xiangming
Objective: To identify quantitative and qualitative differences in the velopharyngeal musculature and surrounding structures between children with submucous cleft palate (SMCP) and velopharyngeal insufficiency (VPI) and noncleft controls with normal anatomy and normal speech. Methods: Magnetic resonance imaging was used to evaluate the velopharyngeal mechanism in 20 children between 4 and 9 years of age; 5 with unrepaired SMCP and VPI. Quantitative and qualitative measures of the velum and levator veli palatini in participants with symptomatic SMCP were compared to noncleft controls with normal velopharyngeal anatomy and normal speech. Results: Analysis of covariance revealed that children with symptomatic SMCP demonstrated increased velar genu angle (15.6°, P = .004), decreased α angle (13.2°, P = .37), and longer (5.1 mm, P = .32) and thinner (4 mm, P = .005) levator veli palatini muscles compared to noncleft controls. Qualitative comparisons revealed discontinuity of the levator muscle through the velar midline and absence of a musculus uvulae in children with symptomatic SMCP compared to noncleft controls. Conclusions: The levator veli palatini muscle is longer, thinner, and discontinuous through the velar midline, and the musculus uvulae is absent in children with SMCP and VPI compared to noncleft controls. The overall velar configuration in children with SMCP and VPI is disadvantageous for achieving adequate velopharyngeal closure necessary for nonnasal speech compared to noncleft controls. These findings add to the body of literature documenting levator muscle, musculus uvulae, and velar and craniometric parameters in children with SMCP.